Solitons and other solutions to Wu–Zhang system - Mirzazadeh, Mohammad; Ekici, Mehmet; Eslami, Mostafa; Krishnan, Edamana Vasudevan Vasudevan; Kumar, Sachin; Biswas, Anjan (Nonlinear Analysis: Modelling and Control, 2017)
This paper addresses Wu–Zhang system to study dispersive long waves. The extended trial equation method extracts solitary waves, shock waves and singular solitary waves solutions. Subsequently, Lie group formalism is also applied to derive symmetries of the Wu–Zhang system and the derived ordinary differential equations are further analyzed to retrieve exact solutions are obtained. Finally, implementation of mapping method secures additional exact solutions.